Reciprocal Relationship Between Calcium Signaling and Circadian Clocks: Implications for Calcium Homeostasis, Clock Function, and Therapeutics - Cavieres-Lepe, Javier; Ewer, John (Frontiers in Molecular Neuroscience, 2021)
In animals, circadian clocks impose a daily rhythmicity to many behaviors and physiological processes. At the molecular level, circadian rhythms are driven by intracellular transcriptional/translational feedback loops (TTFL). Interestingly, emerging evidence indicates that they can also be modulated by multiple signaling pathways. Among these, Ca2+ signaling plays a key role in regulating the molecular rhythms of clock genes and of the resulting circadian behavior. In addition, the application of in vivo imaging approaches has revealed that Ca2+ is fundamental to the synchronization of the neuronal networks that make up circadian pacemakers. Conversely, the activity of circadian clocks may influence Ca2+ signaling. For instance, several genes that encode Ca2+ channels and Ca2+-binding proteins display a rhythmic expression, and a disruption of this cycling affects circadian function, underscoring their reciprocal relationship. Here, we review recent advances in our understanding of how Ca2+ signaling both modulates and is modulated by circadian clocks, focusing on the regulatory mechanisms described in Drosophila and mice. In particular, we examine findings related to the oscillations in intracellular Ca2+ levels in circadian pacemakers and how they are regulated by canonical clock genes, neuropeptides, and light stimuli. In addition, we discuss how Ca2+ rhythms and their associated signaling pathways modulate clock gene expression at the transcriptional and post-translational levels. We also review evidence based on transcriptomic analyzes that suggests that mammalian Ca2+ channels and transporters (e.g., ryanodine receptor, ip3r, serca, L- and T-type Ca2+ channels) as well as Ca2+-binding proteins (e.g., camk, cask, and calcineurin) show rhythmic expression in the central brain clock and in peripheral tissues such as the heart and skeletal muscles. Finally, we discuss how the discovery that Ca2+ signaling is regulated by the circadian clock could influence the efficacy of pharmacotherapy and the outcomes of clinical interventions.